THE SCHOOL ENVIRONMENT AS A LEARNING RESOURCE ON PLANTAE MATERIAL - Ummi Hiras Habisukan; Irham Falahudin; Dini Afriansyah; Dwi Novriani (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2017)
This study aims to determine the benefits of school environment as a source of learning on the Plantae material (Spermatophyta) by using contextual learning on the activities of high school students of high school. This research used descriptive research type. Sampling in this research is done by purposive sampling technique (purposive sampling) considering student ability and activity in various class samples. Research sample in this research is class X MIPA. This research was conducted for three meetings with assessment instrument in the form of observation sheet which will be assessed by 5 (five) observers. The observation sheets are activity observation sheets, student attitudes and skills as well as individual student final reports. The results of this study indicate that the activities of students including active category (B) with 82% percentage of assessment. Likewise the attitude of students who belong to either category (B) with the same percentage of assessment. Another case with the skills of students who are classified as excellent (A) with a higher percentage of assessment that is 89%. Meanwhile, in the final report students individually more than 50% of students category is very good (A) with the percentage of students overall 83.8% which indicates the final report of students done with good category (B). If accumulated as a whole the percentage of assessment of each instrument is 84.42% with good category with the predicate B. Therefore, the school environment can be utilized as a source of biology learning especially Spermatophyta material by using contextual learning model. Keywords: learning, environment, school, learning source, plantae material